TIM-3 plays a more important role than PD-1 in the functional impairments of cytotoxic T cells of malignant Schwannomas - Zhao Li; Xiaobing Liu; Rongbin Guo; Pengfei Wang (Tumor Biology)
Cancer immunotherapy using cytotoxic T cells demonstrates dramatic survival benefits in lymphomas, but its efficacy in solid tumors is limited. Here, we investigated the possibility of using cytotoxic T cells to treat malignant Schwannoma, a rare but aggressive nerve sheath tumor, by examining the native T-cell immunity in the host. We found that compared to CD8 + T cells from healthy controls or benign Schwannoma patients, the CD8 + T cells from malignant Schwannoma patients were present at normal frequencies but were substantially enriched with PD-1 − TIM-3 + and PD-1 + TIM-3 + cells. Compared to the PD-1 − TIM-3 − CD8 + T cells, the PD-1 − TIM-3 + and PD-1 + TIM-3 + CD8 + T cells presented significantly lower proliferation capacity, reduced interleukin 2 and interferon gamma expression, and/or dramatically decreased perforin and granzyme B secretion, indicating a whole-spectrum immunosuppression and reduced cytotoxicity. TIM-3 expression alone was associated with lower proliferation and less perforin and granzyme B secretion, whereas PD-1 expression alone was not associated with functional impairments, suggesting that TIM-3 expression was a better marker of exhausted CD8 + T cells. The expression of galectin 9, a TIM-3 ligand, in CD4 + Th cells was significantly elevated in malignant, but not benign, Schwannoma patients and were enriched in CD25 + Treg cells. Both the PD-1 − TIM-3 + and PD-1 + TIM-3 + CD8 + T cells responded to Treg-mediated and galectin 9–mediated suppression, whereas the PD-1 + TIM-3 − CD8 + T cells only responded to Treg-mediated suppression. In resected tumors, the malignant Schwannomas had more tumor-infiltrating CD4 + and CD8 + T cells than the benign Schwannomas, but a large fraction of these tumor-infiltrating CD4 + and CD8 + T cells expressed PD-1 and/or TIM-3, which indicated that their antitumor immunity was compromised. Together, our results suggested that PD-1 and TIM-3 blockade might be necessary in developing effective immunotherapeutic strategies in malignant Schwannoma, in which TIM-3 may play a more important role.